TEACHING READING COMPREHENSION BY USING CREATIVE THINKING READING ACTIVITIES (CTRA) TO THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 8 LUBUKLINGGAU - . Syaprizal; Yayuk Handira (International Conference on Education and Language (ICEL), 2016)
The problem of this study was “Is it significantly effective to teach reading comprehension by using Creative Thinking Reading Activities (CTRA) to the Eleventh Grade Students of SMA Negeri 8 Lubuklinggau  in the academic year of 2013/2014?”. The objective of this study was to find out whether or not it was significantly effective to teach reading comprehension by using Creative Thinking Reading Activities (CTRA) to the Eleventh Grade Students of SMA Negeri 8 Lubuklinggau in the academic year of 2013/2014. In this study, the writer proposed two hypotheses. They were Nul Hypotheses (Ho) and Alternative Hypotheses (Ha). The method applied was pre-experimental method with one group pre-test post-test design. The sample was taken through cluster random sampling. The number of the sample was 28 students. The data were collected by using test consisting of 20 items of multiple choices. The data obtained were analyzed through three techniques: 1) Individual Score, 2) Minimum Mastery Criteria, and 3) Matched t-test. The results of this study: (1) The mean students’ score in the pre-test was 58.03, (2) The mean score of post-test was 70.17, and (3) the result of matched t-test was 7.05, which was higher than 1.701 of the ttable of 28 with 95% significant level for one tailed-test. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted.